DIFFERENT APPROACHES FOR DARK MATTER HALOS OF CLUSTERS OF GALAXIES - Brilenkov, R.; Eingorn, M.; Zhuk, A. (Одеські астрономічні публікації, 2014)
To describe the density profile of dark matter halos of clusters of galaxies, we compare the approach based on the Schwarzschild-de Sitter metric with a recentlydeveloped mechanical one (discrete cosmology inside the cell of uniformity). In the first approach, the cosmological effects are completely incorporated into the cosmologicalconstant, while in the second one the scale factor enters directly the corresponding equations. Hence, in the latter case we can take into account the effect on the density profiles not only the cosmological constant, but also other material components. Thus, we can evaluate how thisdynamic impact is considerable and testable.